ISG15 fast-tracks DNA replication - Meroni, Alice (J Cell Biol, 2020)
In this issue, Raso et al. (2020. J. Cell Biol. https://doi.org/10.1083/jcb.202002175) uncover a novel replication fork speed regulatory network controlled by the ubiquitin-like modifier interferon-stimulated gene 15 (ISG15), which plays a central role in the innate immune response and regulates tumorigenesis as well as chemotherapy response.